Pengaruh Enviroment Karyawan dan Kepuasaan Pelanggan terhadap Total Quality Management pada UMKM di Cikarang - Dede Farida; Ella Ramadhan; Fitri Sri Khairunnisa; Muhammad Ibnu Ubaidilah; Tiara Maharlica Puteri Amalia; Retno Purwani Setyaningrum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of a positive work environment on customer satisfaction through the implementation of Total Quality Management (TQM) in MSMEs in Cikarang. A positive work environment is measured through [light, sound, etc.]. Customer satisfaction is measured through [conformity to expectations, interest in returning, etc.]. The research method used is quantitative by distributing questionnaires. The results of the study are expected to contribute to the development of a more effective TQM strategy in improving company performance.